2014
DOI: 10.1016/j.jcin.2013.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Endothelial Shear Stress Patterns on Neointimal Proliferation Following Drug-Eluting Bioresorbable Vascular Scaffold Implantation

Abstract: The hemodynamic microenvironment appears to regulate neointimal response following an Absorb BVS implantation. These findings underline the role of the ESS patterns on vessel wall healing and should be taken into consideration in the design of bioresorbable devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 32 publications
2
80
0
1
Order By: Relevance
“…In another BVS study, an inverse association between WSS and NIH was also conferred as a consequence of local hemodynamic milieu on vessel wall healing (Table 3) [30].…”
Section: Bvs Studiesmentioning
confidence: 95%
“…In another BVS study, an inverse association between WSS and NIH was also conferred as a consequence of local hemodynamic milieu on vessel wall healing (Table 3) [30].…”
Section: Bvs Studiesmentioning
confidence: 95%
“…As times goes by, the struts are integrated into the vessel wall and cover by neointima (g and g′). When the shear stress at baseline is portrayed into the follow-up OCT images (g″), it became apparent that the low shear stress areas at baseline (blue) correlate with thicker neointima thickness at follow-up as compared to high shear stress areas (on top of struts in red color), which showed thinner neointima thickness (reprinted from Bourantas et al 93 with permission of the publisher. Copyright © 2014, American College of Cardiology Foundation.…”
Section: Should High-risk Plaque Morphology Direct Revascularization mentioning
confidence: 99%
“…A new layer of neointima and thickening of the fibrous cap overlying the necrotic core was noted (potentially turning a TCFA to thick-cap fibroatheroma; Figure 3). [92][93][94] The pilot SECRITT trial assessed the feasibility and safety of using a self-expandable bare metal stent (vShield) for focal treatment of TCFA. 95 This study showed an increase in the average fibrous cap thickness from 48±12 µm to 201±168 µm at 6-month follow-up, with no MACE associated with the device.…”
Section: Should High-risk Plaque Morphology Direct Revascularization mentioning
confidence: 99%
“…Further examples are glycolide-containing, nanofibrous scaffolds blended with gelatin [31] or hollow fibers blended with poly(ε-caprolactone) (PCL) [32] for vascular tissue engineering, as well as glycolide-based local drug delivery systems [33][34][35]. In addition to these examples it can be pointed that PLA was intensely tested as temporary stent material in cardiology [36,37], vessel surgery [38,39] and urology [40][41][42].…”
Section: Synthetic and Natural Polymersmentioning
confidence: 99%